Oahe Dam, master of the Missouri. - Coon, Martha Sutherland (Irvington-on-Hudson, N.Y. Harvey House, 1969)
A brief section on the history of the Missouri River and efforts to control it is followed by a complete description of the construction of the Oahe Dam, from choosing and preparing the site to the dedication in 1962.
Bibliography: p. 119-120.
Keywords: Oahe Dam (S.D.) -- Juvenile literature; Oahe Dam (S.D.)